2018
DOI: 10.15381/rivep.v29i4.15190
|View full text |Cite
|
Sign up to set email alerts
|

Neospora caninum en llamas de Huancavelica, Perú

Abstract: El objetivo del presente estudio fue determinar, mediante la técnica de Inmunofluorescencia Indirecta (IFI), la frecuencia de anticuerpos frente a Neospora caninum en llamas de la comunidad ganadera de Lachocc, Huancavelica. Se tomó muestras de sangre de 98 llamas hembras adultas, mayores de un año. Los sueros se analizaron mediante IFI empleando un punto de corte de 1:100. Los sueros positivos fueron titulados con diluciones seriadas, determinándose una frecuencia de anticuerpos frente a N. caninum de 12.2% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, nothing is known about the efficiency of vertical transmission of N. caninum in SAC or about the meaning of horizontal transmission through the ingestion of sporulated oocysts shed by canids in these animal species. In Peru, no significant association was found between seropositivity to N. caninum in SAC and age [55,56] or geographical region [57], suggesting that the infection might be mainly transmitted vertically [57]. Apart from some regional studies from Peru, in which higher seroprevalences of infection were reported (17.9-42.4 % in alpacas and 18.4-23.3% in llamas) [58,59], only low seroprevalences were observed in studies outside South America, suggesting that only few animals had contact with the parasite.…”
Section: Discussionmentioning
confidence: 98%
“…However, nothing is known about the efficiency of vertical transmission of N. caninum in SAC or about the meaning of horizontal transmission through the ingestion of sporulated oocysts shed by canids in these animal species. In Peru, no significant association was found between seropositivity to N. caninum in SAC and age [55,56] or geographical region [57], suggesting that the infection might be mainly transmitted vertically [57]. Apart from some regional studies from Peru, in which higher seroprevalences of infection were reported (17.9-42.4 % in alpacas and 18.4-23.3% in llamas) [58,59], only low seroprevalences were observed in studies outside South America, suggesting that only few animals had contact with the parasite.…”
Section: Discussionmentioning
confidence: 98%